O agir docente em contexto de EJA: saberes, gestos e práticas do professor-alfabetizador - Silva, Fabio Pessoa da (2015)
Teaching act, understood as a work, is something that requires an understanding of the multidimensionality constitutive of teaching activity, considered by a sociointeractionist view, which allows to evaluate the individual actions as a reflection of their conceptions/representations built and/or acquired in the social environment. This research focuses on the epistemological approach of the Sociodiscursive Interactionism (SDI) and its main theoretical and methodological contributions, with the assumptions of Bronckart (1999; 2006; 2008); the Work Sciences (the Ergonomy and the Clinic of Activity) , the studies of Clot (2007; 2010); Nouroudine (2002) and Amigues (2004); and Education theories specifically regarding the Didactics, with studies of Tardif (2014); Chevallard (1991; 2013); Aeby-Daghé & Dolz (2008) and Schneuwly (2000). The investigation of this research is focused on the act of the literacy-teacher who works in the Brazil Literacy Programme (Programa Brasil Alfabetizado - PBA). The goal is to understand the teaching practice of literacy-teacher in the context of Youth and Adult Education (Educação de Jovens e Adultos – EJA), considering the relationship between the didactic gestures and teaching knowledge presented in their conceptions and their performances. This aim, based on this relation, is to investigate to what extension an analysis of literacy-teachers’ act in teaching young and old students can reveal their knowledge, specific gestures and practices. In this research, there are two collaborators who work in the PBA at urban schools, in the municipality of Jacaraú-PB. The adopted methodological approach consists of three stages of analysis, including the represented/interpreted work and the performed work. Thus, the collection and provision of data necessarily were carried out through, firstly semi structured interviews to check the teachers’ conceptions and their implied knowledge; secondly, filming three classes of each collaborator to check and categorize didactic gestures mobilized by them. Thirdly, a simple self-confrontation session with both literacy-teachers in order to get their interpretations of the implemented pedagogical act. With all the data, each stage was analyzed separately, using as categories, the thematic content and the linguistic-discursive materialization proposed by the SDI, in Machado and Bronckart (2009), in addition to the founding didactic gestures defined by Aeby-Daghé & Dolz (2008). In the end, there was a triangulation of data, bringing together all realization, in order to get a more accurate view of the investigated object. As conclusions, it was found that there are eight evidenced conceptions in the literary-teachers of the PBA, which are in the base of their specific didactic gestures’ performance. In addition, the interpretations of their own act reveal that the higher is the teaching experience, the higher is the tendency of the educator to shield him/herself and avoid explicitly self-reflections that expose his/her weaknesses and unexpected actions in their pedagogical activity. Therefore, as a result of all the analysis after triangulation, it was found that experiential knowledge derived from practice in the classroom is what permeates and guides the generation, doing and interpretation of these literacy-teachers of young people and adults. This fact confirms the thesis that pedagogical practice of the literacy-teachers of young and adult students in the Literate Brazil Program is permeated by didactic gestures and acquired and (re)focused knowledge, mainly in / by the experience in the classroom.